Assessing the scales in numerical weather and climate predictions: will exascale be the rescue?. (8th April 2019) - Neumann, Philipp; Düben, Peter; Adamidis, Panagiotis; Bauer, Peter; Brück, Matthias; Kornblueh, Luis; Klocke, Daniel; Stevens, Bjorn; Wedi, Nils; Biercamp, Joachim
Abstract : We discuss scientific features and computational performance of kilometre-scale global weather and climate simulations, considering the Icosahedral Non-hydrostatic (ICON) model and the Integrated Forecast System (IFS). Scalability measurements and a performance modelling approach are used to derive performance estimates for these models on upcoming exascale supercomputers. This is complemented by preliminary analyses of the model data that illustrate the importance of high-resolution models to gain improvements in the accuracy of convective processes, a better understanding of physics dynamics interactions and poorly resolved or parametrized processes, such as gravity waves, convection and boundary layer. This article is part of the theme issue 'Multiscale modelling, simulation and computing: from the desktop to the exascale'.